Comparative analysis of the phytochemical and physicochemical properties of herbal-infused oils (Agriculture, Food, and Natural Resources Journal, 2025)
Infused oils with plant extracts are well-known for diverse applications, particularly for their therapeutic and cosmetic purposes; herbal oil infusion enhances the bioactive and physicochemical properties of oils, influencing their suitability for cosmetic and dietary applications. This study evaluates the phytochemical and physicochemical properties of herbal infused oils to determine their stability and potential uses. The infused oils were prepared using selected medicinal plants: turmeric, lemon, neem, carrot, and acalypha, with olive oil as the carrier. Phytochemical screening was conducted to identify bioactive compounds, while physicochemical parameters such as acid value (AV), saponification value (SV), iodine value (IV), peroxide value (PV), and ester value (EV) were assessed following standard analytical procedures. Phytochemical screening revealed terpenoids in all infused oils, while alkaloids, anthraquinones, and steroids were present in specific samples. Tannins, flavonoids, glycosides, and phenols were not detected. Physicochemical analysis showed significant (p
Keywords: Cosmetics; Herbal oils; Oxidative stability; Quality